The Contribution of Islamic Banks in Supporting Green Economy Initiatives and Sustainable Financial Growth - Dwiki Alfianto; Trinandari Prasetyo Nugrahanti; Muzaffar Tuyginov Nozim ugli (Green Economics: International Journal of Islamic and Economic Education, 2024)
This study investigates the contribution of Islamic banks in supporting green economy initiatives and promoting sustainable financial growth. Employing a quantitative research design, the study utilizes secondary data collected from annual reports, sustainability disclosures, and carbon emission reports of Islamic banks for the period 2018–2024. The research aims to examine the relationship between green financing portfolios and key financial performance indicators Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR) while evaluating the environmental impact through carbon emission reduction. Descriptive statistics provide an overview of green financing activities and financial ratios, while multiple regression analysis assesses the effect of green financing on sustainable financial performance, controlling for bank size, Gross Domestic Product (GDP) growth, and inflation. An independent sample t-test compares Islamic and conventional banks in terms of ethical compliance, environmental contribution, and profitability. The findings reveal that Islamic banks allocate a higher proportion of financing to green projects, achieving significant carbon emission reductions without compromising financial performance. The green financing portfolio exhibits a positive and significant effect on sustainable financial growth, and larger banks demonstrate a greater capacity to implement sustainability initiatives. The comparative analysis confirms that Islamic banks outperform conventional counterparts in environmental and ethical dimensions while maintaining comparable profitability. These results underscore the potential of Sharia-compliant banking to integrate ethical, environmental, and economic objectives, positioning Islamic financial institutions as key actors in advancing a sustainable, low-carbon financial system.